Hypervalent Iodine(III)-Catalyzed Synthesis of 2-Arylbenzofurans - Singh, Fateh V.; Mangaonkar, Saeesh R. (Synthesis, 2018)
An alternative route for the synthesis of 2-arylbenzofurans is described by iodine(III)-catalyzed oxidative cyclization of 2-hydroxystilbenes using 10 mol% (diacetoxyiodo)benzene [PhI(OAc)2] as catalyst in the presence of m-chloroperbenzoic acid. The 2-arylbenzofurans were isolated in good to excellent yields.
Keywords: cyclization reactions; o-hydroxystilbenes; 2-arylbenzofurans; hypervalent iodine reagents; hypervalent iodine catalyst